Improvement of Marketing Strategy for Medali Mas ikat weaving craft Through SWOT Analysis - Arinda, Firda Ayu; Fauji, Diah Ayu Septi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research Aim : This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) of Medali Mas ikat weaving craft and formulate effective and efficient marketing strategies to optimize marketing and appeal to the younger generation. Method: The method used is quantitative with an observational descriptive approach. Data was collected through interviews, observations, and documentation, and analyzed using SWOT analysis. Results: The results of the analysis show that Medali Mas ikat weaving craft has strengths in product quality and design uniqueness, but faces weaknesses in marketing and production. Opportunities for collaboration with designers and influencers as well as challenges from younger generation's interest in traditional products were identified. Theoretical  contribution/Originality: This study provides a deeper understanding of the application of SWOT analysis in the context of small and medium enterprises (SMEs) in Indonesia, as well as filling in the gaps in the literature related to culture-based marketing strategies. Practitioner Implication: These findings can be used by business practitioners to formulate more targeted marketing strategies, as well as provide recommendations for government policies in supporting SMEs that focus on cultural products.